The Association between Cadmium Exposure and Thyroid Function in Animals: A Systematic Review - Nazarian, Maryam; Mohammadparast-Tabas, Pouria; Harifi-Mood, Mohammad Sadra; Aramjoo, Hamed; Bavali-Gazik, Ahmad; Saberi, Amirhossein; Peyghambari, Yasaman; Mohammadparast-Tabas, Peyman; Anghoshtary, Amirhosein; Samarghandian, Saeed; Farkhondeh, Tahereh (Current Molecular Medicine, 2025)
BackgroundSeveral studies have indicated an association between cadmium (Cd) exposure and the induction of thyroid dysfunction in animal models.Objective and AimsThere are inconsistent findings on the effect of Cd on the thyroid gland. Therefore, this systematic study was designed to determine the association between changes in thyroid function markers and Cd exposure in animals.MethodsThe search was performed on Scopus, PubMed, Web of Science and databases, and Google Scholar until May 2023. Studies on the relationship between Cd exposure and fish's thyroid function were conducted on rodents and fish.ResultsIn total, 171 articles were obtained from the main databases using the search strategy mentioned in this study. Finally, 24 articles were selected according to our inclusion criteria for systematic studies. The findings indicated an increase/decrease or no change in triiodothyronine (T3), thyroxine (T4), and thyroid stimulating hormone (TSH) levels in rodents, fish, and animals exposed to Cd.ConclusionOur findings indicated an association between Cd exposure and thyroid dysfunction in rodents, fish, and other animals. However, the association between urinary and blood Cd levels and thyroid function remains unclear in humans because of controversial findings and a lack of strong mechanistic evidence. We perform large cohort human studies to the answer to this question.
Keywords: TSH